READINESS AND INVOLVEMENT OF EARLY CHILDHOOD TEACHERS IN EAST JAVA DURING THE COVID-19 PANDEMIC THROUGH ONLINE LEARNING - Kristin Anggraini (Widya Mandala Surabaya Catholic University, 2021)
Since the beginning of 2020, the world has been shaken by an incident, namely the spread of the Covid-19 virus. The spread of the Covid-19 virus is very widespread throughout the world, so the World Health Organization (WHO) conveyed this as a threat to the world on January 31, 2020 which was later announced to be a pandemic for the international community, namely on March 11, 2020 (Shan L. Pana et al, 2020). The Indonesian government finally took part in handling the spread of the Covid-19 virus, including by recording the area where the virus spread and mapping it into several zones (Kemenkes, 2020). Because of some areas in East Java are mostly in the red and orange zones, which are areas with a high and dangerous spread of the Covid-19 virus, the researchers wanted to know the readiness and involvement of early childhood teachers in East Java during the COVID-19 pandemic through online learning. This research is a qualitative descriptive study that uses data collection techniques through literature review and surveys. Furthermore, all data collected from both the literature review and survey results were analyzed for description. The survey results state that the activities that have been planned in the lesson plan can be carried out well. However, there are parents of students who often do not collect student assignments on time, resulting in teachers having difficulty in assessing each student. Good ICT mastery can facilitate the implementation of online learning activities and early childhood teachers also support the implementation of online learning from home imposed by the Government to suppress the spread of the Covid-19 virus.